The potential for Entomophaga maimaiga to regulate gypsy moth Lymantria dispar (L.) (Lepidoptera: Erebidae) in Europe. (13th February 2016) - Zúbrik, M.; Hajek, A.; Pilarska, D.; Špilda, I.; Georgiev, G.; Hrašovec, B.; Hirka, A.; Goertz, D.; Hoch, G.; Barta, M.; Saniga, M.; Kunca, A.; et al.
Abstract: Gypsy moth, Lymantria dispar L., is one of the most important pests of deciduous trees in Europe. In regular cycles, it causes large‐scale defoliation mostly of oak, Quercus spp., forests. Government authorities in the most infested countries in Europe conduct large‐scale applications of pesticides against gypsy moth. In 1999, a new natural enemy, the entomopathogenic fungus Entomophaga maimaiga, was successfully introduced into a gypsy moth population in Bulgaria. Recent investigations suggest that now E. maimaiga is quickly spreading in Europe. Herein, past studies are reviewed regarding this fungus with special emphasis on its potential for becoming an important factor regulating gypsy moth populations in Europe, focusing on the host's population dynamics in relation to the fungus, the influence of environmental conditions on fungal activity, the influence of E. maimaiga on the native entomofauna, including other gypsy moth natural enemies, and spread of the fungus. Based on this analysis, the potential of E. maimaiga for providing control in European gypsy moth populations is estimated.